Effects of neurofeedback in the management of chronic pain: A systematic review and meta‐analysis of clinical trials. (30th June 2020) - Patel, Kajal; Sutherland, Heather; Henshaw, James; Taylor, Jason R.; Brown, Christopher A.; Casson, Alexander J.; Trujillo‐Barreton, Nelson J.; Jones, Anthony K. P.; Sivan, Manoj
Abstract: Background and Objective: Neurofeedback (NFB) provides real‐time feedback about neurophysiological signals to patients, thereby encouraging modulation of pain‐associated brain activity. This review aims to evaluate the effectiveness and safety of NFB in alleviating pain and pain‐associated symptoms in chronic pain patients. Methods: MEDLINE, PUBMED, Web of Science and PsycINFO databases were searched using the strategy: ("Neurofeedback" OR "EEG Biofeedback" OR "fMRI Biofeedback") AND ("Pain" or "Chronic Pain"). Clinical trials reporting changes in pain following electroencephalogram (EEG) or functional magnetic resonance imaging (fMRI) NFB in chronic pain patients were included. Only Randomized‐controlled trials (RCT), non‐randomized controlled trials (NRCT) and case series were included. Effect size was pooled for all RCTs in a meta‐analysis. Results: Twenty‐one studies were included. Reduction in pain following NFB was reported by one high‐quality RCT, five of six low‐quality RCT or NRCT and 13 of 14 case‐series. Pain reduction reported by studies ranged from 6% to 82%, with 10 studies reporting a clinically significant reduction in pain of >30%. The overall effect size was medium (cohen's d −0.76, 95% confidence interval −1.31 to −0.20). Studies were highly heterogeneous (Q [ df = 5] = 18.46, p = .002, I 2 = 73%). Improvements in depression, anxiety, fatigue and sleep were also seen in some studies. Common side‐effects included headache, nausea and drowsiness. These generally did not lead to withdrawal of therapy except in one study. Conclusions: Neurofeedback is a safe and effective therapy with promising but largely low‐quality evidence supporting its use in chronic pain. Further high‐quality trials comparing different protocols is warranted to determine the most efficacious way to deliver NFB. Significance: Neurofeedback is a novel neuromodulatory approach which can be used to reduce the severity of pain and pain‐associated symptoms such as sleep disturbances, mood disturbances, fatigue and anxiety in a number of chronic pain conditions. It has a potential to provide integrative non‐pharmacological management for chronic pain patients with pain refractory to pharmacological agents with high side‐effect profiles. Further high‐quality double‐blinded randomized sham‐controlled trials are needed in order to fully explore the potential of this therapy.